Analysis Of Advertising And Sales Promotion On Purchase Decisions At PT. Alfamart Lampung - Ulfa Fitriyani Yapan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to determine how consumers' perceptions of advertising and sales promotions carried out by the company, the influence of advertising on purchasing decisions and to determine the influence of sales promotions on purchasing decisions. Research by the author is at PT. Alfamart with customer population in Lampung province. Selection of respondents as research objects related to customers of PT. Alfamart in Lampung using the Slovin method, this study got 43 respondents. Questionnaire data collection method. Data processing techniques are used to assist SmartPLS data processing software. The results showed that the values ​​obtained from the coefficient table path, X1 (AD) to Y (purchase decisions) were 0.856. This indicates that advertising has a positive effect, and the p value of 0.000 means that the advertising variable is significant. In the path coefficient table, X2 (sales promotion) to Y (purchase decision) from -0.021. This shows that sales promotion has a negative effect and the p value is 0.846, it is greater than 0.05, so the sales promotion variable is negative and not significan.